PENGARUH PENERIMAAN PAJAK, EKSPOR DAN IMPOR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA PADA TAHUN 2000 - 2016 - Denno Darmantyo (Jurnal Ilmu Ekonomi JIE, 2018)
Abstract The purpose of this research is to analyze and describe how the effect of tax income, exports and imports on economic growth in Indonesia.The instrument Analysis used multiple linear regression method with OLS (ordinary least squares) method by using time series data. The method test using  the classical assumption test and statistical test. From the analysis results obtained that the effect of tax income is has negatively effect and exports have a positive effect while imports have a negative effect. Simultaneously of all these variables have a significant effect on economic growth in Indonesia.The conclusion of this reserch explains that all of variables, tax and import variables have a significant negative effect on economic growth, and the variable that positively effect on economic growth in Indonesia is export variable.